Potential risk of adverse event in patients undergo elective urologic surgery - Ratih Wulansari, Ratih Wulansari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Almost all medical treatment may pose risk. The risk of adverse event in patients undergoing surgery is higher than those who undergo non surgical intervention. The incidence of adverse event varies from 3.7% in the US to 16.7% in Australia. Basically, most of the adverse events are preventable. It is therefore recommended to implement clinical risk management in health care services. Objective: To identify risk of adverse event among patients undergo elective urologic surgeryMethod: A cross sectional study was carried out to collect prospective data on patients underwent elective urologic surgery at Tabanan General Hospital between August-September 2005. Data on the risk of adverse event were identified since patients were admitted to Hospital, underwent pre-op preparation and surgical procedure. Follow up was carried out until 30 days after surgical procedureResult: Seven major potential risks were identified, i.e.(1) pre-operative stay> 3 days (28.85%);(2) patients risks for surgery (44.23%); (3) prophylactic antibiotic were given > 2 hours before surgery (88.46%); (4) ASA > (82.69%); (5) preoperative hair removal > 2 hours before surgery (86.53%); (6) use of intravenous line more than 24 hours (26.92%); and (7) use of urine cathether > 6 days (25%). It is found that pre-operative stay > 3 days was significantly related to the occurrence of adverse event.Conclusion: Pre-operative stay > 3 days contributed significantly in the occurrence of adverse event among patients underwent elective urologic surgery. However, other risk factors were not significantly related to adverse event due to small sample size.Key words: elective urologic surgery - risk - clinical risk management - clinical governanceÂ